2023
DOI: 10.3390/app132011503
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Effect of Temperature on FDM 3D Printing Polymers: ABS, PETG, and PLA

Ryan Mendenhall,
Babak Eslami

Abstract: Four-dimensional printing is a process in which a 3D-printed object is intentionally transformed in response to an external stimulus such as temperature, which is useful when the final geometry of a 3D-printed part is not easily manufacturable. One method to demonstrate this is to print a part made of thin strips of material on a sheet of paper, heat the part, and allow it to cool. This causes the part to curl due to the difference in the thermal expansion coefficients of the paper and plastic. In an attempt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…FDM involves melting a polymer and dropping it in a modeling orifice or mold [ 73 ]. A drop of the molten polymer is consistently added to the FDM machine until the desired material shape and size are achieved [ 74 ].…”
Section: Systematic Review and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…FDM involves melting a polymer and dropping it in a modeling orifice or mold [ 73 ]. A drop of the molten polymer is consistently added to the FDM machine until the desired material shape and size are achieved [ 74 ].…”
Section: Systematic Review and Analysismentioning
confidence: 99%
“…The findings consistently demonstrate that combining recycled polymers can produce 3D printing filaments with exemplary mechanical properties. Nonetheless, according to Mendenhall and Eslami [ 73 ], repeated heating reduces the radius of curvature of the material. Per Figure 3 , [ 73 ] demonstrated that the radius of curvature decreases as the material is heated repeatedly at gradually increasing temperatures.…”
Section: Systematic Review and Analysismentioning
confidence: 99%
See 3 more Smart Citations